THE ANALYSIS OF CRM STRATEGY ON COMPANY IMAGE - Hendrajaya Hendrajaya (Jurnal Ekonomi dan Bisnis, 2010)
This study aimed at explaining both the direct and indirect influences of Customer RelationshipManagement strategy on company image through customer satisfaction. This researchwas conducted in service user customers of PT BGR Semarang. It used observation, questionnaireand documentation methods, while the data was analyzed using descriptive analysisand multiple linear regressions. From the research result, it was found that sig calculation0.013<0.05 in which H1 was confirmed and 0.21<0.05 in which H2 was confirmed; it meansthat there were positive influences of CRM on customer satisfaction and that there were positiveinfluence of CRM strategy on company image through customer satisfaction. The saidresearch result could be explained that the well-implemented CRM strategy would likely tocreate customer satisfaction. The suggestions the researcher could offer were. For the companyto improve CRM strategy approaches such as: (1) improving the use of marketing mix,particularly service product, (2) improving communication with customers periodically or onmonthly basis, (3) improving the service particularly that from employees and continuouslydeveloping the image by considering the aspects of: company’s social responsibility towardits environment and warehouse, innovating, in this case, by improving support equipmentsand devices, improving management quality, particularly HR.Keywords: Customer Relationship Management, Company Image, Customer Satisfaction